Manajemen Asuhan Keperawatan Pada Anak Dengan Disfungsi Kardiovaskular (Congestive Heart Failure) Pada Anak : Literature Review - Setyawati, Ari; Marwiati, Marwiati (Jurnal Ilmiah Kesehatan, 2017)
Background: Heart failure in children is an important cause of morbidity and mortality in childhood (Office et al., 2013). The most likely cause of a child's congestive heart failure depends on his or her age. Neonates and young infants from 2 months of age are the most likely age range for congestive heart failure associated with structural heart disease (Satou, 2015). The purpose of this literature review is used to analyze the importance of critical care with cardiovascular issues "Congestive Heart Failure" in children nursing care management. Method: The literature review method is done by searching the journal by finding 20 articles, then the filter for the last 5 years article got 5 and selected 3 articles assessed by the author related to the keywords congestive heart failure. Results: Physiological monitors in hospitals can alert health workers for early signs of physiological damage, and thus have great potential for life-saving in patients with fatique heart failure. Keywords: Congestive Heart Failure, nursing care.